Institutional pressure and low carbon innovation policy: the role of EMS, environmental interpretations and governance heterogeneity - Yuning, Mu; Taozhen, Huang; Saleem, Nayab; Hassan, Abdul Hanan (Frontiers in Environmental Science, 2024)
As the global community deals with the urgent need for sustainable development, the formulation and implementation of effective low carbon innovation policies have emerged as a critical challenge. However, the extant literature is unclear in examining low carbon innovation policy. Underpinned by institutional theory, the current study addresses the role of institutional pressure in the development of low carbon innovation policies. Additionally, the study examines the role of environmental management systems as a mediation and environmental interpretations and governance heterogeneity as moderators. Methodologically, the data were collected from the manufacturing sector of Pakistan. The findings suggest that institutional pressure greatly influences low carbon innovation policies. Furthermore, the findings from environmental management systems strongly suggest that they significantly encourage institutional pressure on low carbon innovation. Additionally, the roles of environmental interpretations and governance heterogeneity have a significant effect on the relationship.